A psicanálise em cursos de pedagogia - Andre Julio Costa (2013)
The psychoanalytic ideas have been occupying space in the educational circuit and in the educational processes of children. So it becomes necessary to understand the importance of psychoanalysis for the life of a pedagogue, and the training that is offered for this professional. The increasing numbers of research it as a proof showing that the field of psychoanalytic studies is increasingly sedimented within education. This sediment can be perceived when we detect psychoanalysis occupying spaces in the discussions of the field of teacher education and within their own curriculum of pedagogy in the form of disciplines. The idea of bringing psychoanalysis to train educators is not to propose that the teacher has the role of analyst strict sense, but rather to provide a device to interrogate the totalizing conceptions of education for the benefit of an intervention that favors uniqueness. We seek in the history of psychoanalysis identify how these were related to education, and with the training of teachers. Given the objective of understanding the integration of psychoanalysis courses in pedagogy, we analyze the disciplines, mandatory and optional, Psychoanalytic Education and three Brazilian public universities located in the Southeast. In addition to analyzing the entire program of courses, we interviewed the teachers responsible for such. The interviews sought to understand the disciplines and their development, but also the trajectory of teachers, space and resistance of psychoanalysis within faculties of education, beyond the perception that teachers have about their students. Analyses of the data show that the disciplines of psychoanalysis are very concerned to show what is not within his authority, what psychoanalysis does not, being too marked by conceptual discussions, especially on children, but with few implications of the place that teacher occupies in teaching and learning. Psychoanalysis is called to be part of the curriculum of pedagogy from his contributions on the formation of children and respect the teacher with your own personal design, while the second has a greater relevance to the training and teaching practice. So, as a proposal for pedagogy courses bring the discussions of the clinical method as one of the possibilities to work within the psychoanalytic theories of teacher education.